Avaliação da capacidade leishmanicida de neutrófilos sobre a Leishmania (Leishmania) amazonensi in vitro e em um modelo de resistência in vivo - Carmo, Érico Vinícius de Souza [UNIFESP] (2010)
The present study focused on the role of neutrophils in Leishmania (Leishmania) amazonensis infection by use of susceptible (BALB/c) and resistant (C3H/HePas) mouse strains. Comparison of the outcome of L. (L.) amazonensis infection between the two mouse strains demonstrated a gradual increase of foot lesions in BALB/c mice, whereas the disease did not develop in the C3H/HePas strain. Histopathological analysis of foot lesions showed a predominance of macrophages harboring a high number of L. (L.) amazonensis amastigotes, few lymphocytes and neutrophils and hyperplasia of epithelial cells in BALB/c mice. In contrast, an intense inflammatory reaction with a large infiltrate of neutrophils, an initial granulomatous process exhibiting epithelioid cells and lymphocytes and rare L. (L.) amazonensis amastigotes were observed in C3H/HePas mice. Kinetics of in vitro infection of bone marrow macrophages was carried out in the presence or in the absence of IFN-! and showed increased parasite burden in the cultures from both mouse strains. These results demonstrated that the resistance of C3H/HePas mice to L. (L.) amazonensis could not be attributed either to an intrinsic mechanism of L. (L.) amazonensis macrophage destruction or to the macrophage activation by IFN-!. An effective destruction of L. (L.) amazonensis amastigotes was observed in cocultures of macrophages with inflammatory neutrophils in vitro. The leishmanicidal activity of the cocultures did not depend on the animal resistance profile since the parasite destruction was similar when cells were obtained from BALB/c or C3H/HePas mice. Furthermore, amastigote killing did not require contact between infected macrophages and neutrophils, indicating that the parasite destruction is mediated by soluble factors. The cytokine analysis showed that the MCP-1 protein was detected in the supernatants of macrophages 24 hours after infection with L. (L.) amazonensis, whereas secretion of IL-6 and TNF-! indicated a predominance of an inflammatory environment in the cocultures. These results were corroborated by the significant inhibition of the leishmanicidal activity of the cocultures in the presence of anti-TNF- !. However, the L. (L.) amazonensis destruction did not depend on generation of nitric oxide, superoxide or oxygen peroxide, indicating that parasite clearance did not involve the classical pathway of macrophage activation by TNF-!. The implication of neutrophil elastase (NE) and platelet activating factor (PAF) in parasite destruction in the cocultures was also demonstrated. The cytokine analysis in the foot lesions of BALB/c and C3H/HePas strains infected with L. (L.) amazonensis showed an early secretion of TGF-! in BALB/c mice whereas TNF-" predominated in the C3H/HePas strain. These results support our initial observations on the persistence of an inflammatory environment in foot lesions of C3H/HePas mice with infiltration of neutrophils resulting in L. (L.) amazonensis destruction. Depletion with anti Gr-1 in BALB/c and C3H/HePas mice led to a significant decrease of neutrophils in both mouse strains but did not change the course of L. (L.) amazonensis infection. On the other hand, the neutrophil activation with KC delayed the development of foot lesions in BALB/c mice. In conclusion, our data demonstrated that interaction between neutrophils and L. (L.) amazonensis-infected macrophages induces an effective parasite destruction. It is still important to emphasize that our findings opened perspectives to explore the role of innate immunity in L. (L.) amazonensis infection and the C3H/HePas strain constitutes an useful tool for the extension of this study.